Fighting international harmful tax competition beyond the OECD: the role of the civil society - Capone, Rodrigo Senne (2014)
The present dissertation is about International Tax Competition and its harmful effects, the role of International Organizations such as the Organisation for Economic Cooperation and Development – OECD and the Organized Civil Society in the fight against the damaging impacts of this international phenomenon. In a globalized era where technology plays a significant role, with the mobility of capital and the easy flow of investments, many tax systems are structured to offer benefits for non-resident investors, “poaching” other countries’ tax bases. The effects of these advantages offered are mostly harmful, since most taxpayers that take advantage of these harmful tax reducing schemes continue to utilize a particular country’s structure and the public services it offers, but end paying low or no taxes in these jurisdictions. The effects of these malpractices are very damaging to the global tax system, resulting in erosion that impairs the countries’ financial health and in many cases, it can also impact several countries’ social policies once they end up collecting fewer taxes that they should. These non-collected taxes could be invested in social programs to combat usual problems such as hunger, poor public health systems, security, education, and many others. And that is why the international community is discussing and researching this phenomenon trying to find ways that can lead to a harmonization of the international tax scenario, especially when the subject is harmful tax competition and its damaging effects. But not only Governments and International Organisms are involved in this cause. The Civil Society, through its organizations, has been working on these issues looking for better tax practices, normally directing more of their attention to the situation of poorer countries, since they have more difficulties in addressing these issues due to their lack of resources both to fight the harmful tax competition and to research solutions for it. One of the most active Civil Society’s Organization is the Tax Justice Network, which plays a significant in studying and publishing impactful reports on how the harmful tax practices affects countries’ economies, in an effort to achieve tax justice and fairness at a global level, alongside to dozens of others Civil Society’s Organizations spread around the World.